Implementation of Low-Cost Laboratory in Education: A Systematic Literature Review - Fajrin, Suryadi; Hakim, Dadang Lukman (Fakultas Teknik Universitas Negeri Malang, 2022)
In developing countries, the need of practical facilities such as teaching aids and laboratories equipment is still a problem in education. This Inadequate laboratory equipment will affect learning outcomes, and the quality of graduates. The high price of commercial equipment is one of the factors. Therefore, there has been a lot of research to develop low-cost laboratory. This article aims to review the development of low-cost laboratory and how they have implemented in learning. The Systematic Literature Review method is used to overview the implementation of low-cost laboratories in the learning. The synthesis of articles refers to the PRISMA 2020 guidelines. The published articles used in this study were obtained from the IEEE Xplore database for publication from 2017 – 2021. After the articles are selected using inclusion and exclusion criteria, 32 articles were obtained for use. The results of this study indicate that a low-cost laboratory can be an alternative solution to the high price of commercial equipment, and as a learning aid to improve learning outcomes. The methods used in implementing low-cost laboratories are design, research and development and experimentation. The use of low-cost laboratories in learning activities shows a positive impact on improving the quality of learning outcomes